On the identity of Photophilus Folkmanová, 1928: A new generic synonymy (Chilopoda: Geophilomorpha: Geophilidae) - Dányi, László; Tuf, Ivan Hadrián (Zootaxa, 2017)
The enigmatic monotypic genus Photophilus Folkmanová, 1928 and its type species, Photophilus griseus Folkmanová, 1928, were described almost 90 years ago from the Czech Republic. The new genus was erected not only based on some morphological characters, but also on behavioural features rather peculiar among Central European geophilomorphs. Although the patria of these taxa is among the best studied regions regarding Chilopoda, and focussed effort has been made to collect further representatives of these taxa, none have been found since the original description As the type material is lost and we failed to collect new specimens from the type locality, we tried to elucidate the true identity of these genus and species by analysing the characters given in the original description in comparison to all other geophilomorphs known from Europe. The structure of the mouth-parts, the shape of the ventral pore-fields and the arrangement of the coxal pores indicate Photophilus to be in the closest relation with the genus Geophilus Leach, 1814 from which it is separated by characters which are shown here as artefacts or misinterpretations according to the judgement of the original descriptions illustrations. Considering the remaining characters of Photophilus and its type species—including the behavioural features—they actually fit only to the widespread European species Geophilus carpophagus Leach, 1815, which is formerly proposed here to be the subjective senior synonym of Photophilus griseus Folkmanová, 1928 (syn. nov.). Photophilus is formerly proposed here as subjective junior synonym of Geophilus (syn. nov.).